Problems of Literary Language and Culture Language in the Journal "Hylli I Dritës" (1913-1944) - Kastrati, Suela (Mediterranean Journal of Social Sciences, 2012)
This article speaks of the language items addressed in the journal. "Hylli I Dritës" (1913-1944), dedicated to the problem ofliterary and cultural language, the point of view of that period and that the problem is still present today. Magazine "Hylli I Dritës" will beestablished one year after the declaration of Independence (1913). Albanian linguistics in this period will be faced with the task that laythe delivery of language, its teaching in schools. Literary Commis Shkodra (1916-1917) set out some key spelling rules that contributedto the further rapprochement of the two dialectal variants. In the magazine "Hylli I Drites" will be published articles on literary languageproblem (Justin Rrota). He addressed several issues of grammar, the morphology, syntax Historical (Justin Rrota). Articles werepublished by local and foreign scholars on the origin and the origin of Albanian name (Sirdani M., K. Floqi, E. Çabej, O. Myderrizi). Theytreated the problem of Albanian language and its relation to other languages (K. Flloqi, Caragata, N. Jokl, etc..).Wording was collectedby Alexander Sirdani. Efforts were made to the publication of the Gelasiusit toponomastik vocabulary.Articles were published incharacter orthographic, phonetic, phonological, (V.Dukagjini, Marlaskaj, Rrota , Jam). Numerous articles were published on the history ofthe Albanian alphabet and written by writers ranging from early fifteenth century and to the Congress of Monastir (Rrota). Even indialektologjisë will be published the article "For the Albanian linguistic Atlas" by Benedict Dema. Temporary "Hylli I Dritës" is also knownfor its patriotic activities and outstanding contributions to our culture, in awakening the national spirit, the problems struck, bringing theconcerns of many Albanians, in particular of some writers that time that affected the "injustices" that is becoming our national language.An article that tackles this issue is the article "Who are we disfigure the language" written by Antonin Fishta in 1933.